Mood and disruptive behavior disorders and symptoms in the offspring of patients with bipolar I disorder - NESLIHAN INAL-EIROGLU, F. (Masson Italy, 2008)
The study aimed to ascertain the prevalence of mood and disruptive behavior disorders and symptoms in 35 children of 29 adult outpatients with a DSM-IV diagnosis of bipolar I disorder, compared with 33 children of 29 healthy adults, matched with patients on age, socioeconomic status and education. The offspring of bipolar patients had a 9.48 fold higher risk of receiving a psychiatric diagnosis. While only two children of patients with bipolar disorder were diagnosed with a mood disorder, 30.9% displayed mild depressed mood, compared with 8.8% of the controls, a statistically significant difference. The bipolar offspring also scored significantly higher on the hyperactivity and conduct problems subscales as well as the ADHD index of the Conners’ Teacher Rating Scale. The disruptive behavior and mood symptoms observed in early life in the offspring of bipolar patients may indicate the need for early psychosocial intervention.